Effects of Crop Rotation on Spring Wheat Yield and Pest Occurrence in Different Tillage Systems: A Multi-Year Experiment in Finnish Growing Conditions - Jalli, Marja; Huusela, Erja; Jalli, Heikki; Kauppi, Katja; Niemi, Mari; Himanen, Sari; Jauhiainen, Lauri (Frontiers in Sustainable Food Systems, 2021)
Crop rotation and soil tillage are among key factors impacting cropping system productivity, pest management and soil health. To assess their role in northern cropping systems, we quantified the effects of crop rotation on spring wheat yield in different tillage systems based on a long-term (2005-2017) field experiment in southwestern Finland. In addition, effects of crop rotation on weeds, plant pathogens, and pest insects were assessed. Three types of crop rotations were compared: monoculture (spring wheat), two-year rotation (spring wheat – turnip rape – spring wheat – barley) and four-year rotation (spring wheat – turnip rape – barley – pea) under no-tillage and plowing. A diversified crop rotation improved spring wheat yield by up to 30% in no-tillage and by 13% under plowing compared with monoculture. Overall, the yield quantity and quality differences between crop rotations were higher in no-tillage plots than in plowed plots. The occurrence of weed species in spring wheat before herbicide control was highest in the four-year crop rotation and lowest in the wheat monoculture. For plant diseases, wheat leaf blotch disease severity, mainly caused by Pyrenophora tritici-repentis, was lowest in the most diverse crop rotation. On average, wheat leaf blotch disease severity was 20% less when wheat was grown every fourth year compared with wheat monoculture. The effect of crop rotation on stem and root diseases became apparent after six years of rotation and the disease index was lowest in the most diverse crop rotation. Neither rotation nor tillage affected the control need of wheat midge (Sitodiplosis mosellana). Based on our results, diverse crop rotations including cereals, oilseed crops, and legumes increase yield and reduce plant disease severity of spring wheat in Finland, with the magnitude being larger in no-tillage systems.